Radiologiska tecken vid lungödem hos hund och katt - Williams, Elna (2003)
To determine if the descriptions of lung oedema in the literature accurately describe the presence and frequency of radiologic signs, thoracic radiographs of 55 dogs with mitral regurgitation due to endocardiosis (ME), 46 dogs with dilated cardiomyopathy (DCM), 9 dogs with hunting oedema, and 20 cats with hypertrophic cardiomyopathy (HCM) were analysed. The location, type (diffuse or patchy, without or with air bronchograms) and presence of pleural oedema, bronchial wall thickening, widened pulmonary veins, and heart enlargement with subjectively and by the VHS measurement, were determined, and analysed by chi squared test with respect to disease. The dogs nearly always had diffuse oedema, whereas 35% of the cats had a patchy pattern, which agreed with the literature. The common occurrence of cranioventral and caudioventral oedema in heart failure was not described. Pleural oedema, seen in approximately half the dogs, was more common than indicated in the literature, as was also bronchial thickening. As ventral location, thickened bronchial walls and pleural thickening are associated with other diseases than lung oedema, the diagnosis of cardiogenic oedema may rely on the detection of heart enlargement. The consensus reading agreed well with the VHS measurement, but the unexperienced reader would benefit from the VHS except in the case of the dachshund, where 4 were measured as normal despite obvious left atrial enlargement. Dachshunds may require a separate normal range.